The The Relationship Knowledge And Attitude Of Cleaning Service With The Use Of Personal Protective Equipment In Handling Solid Medical Waste At Rotinsulu Lung Hospital Bandung - Gunawan, Iwan; Yogisutanti, Gurdani; Hotmaida, Linda (Jurnal Ilmu Kesehatan Immanuel, 2023)
Cleaning service are people who maintain the cleanliness and health of the hospital environment, one of which is the handling of medical waste. In carrying out this task, it is important for cleaners to use personal protective equipment correctly and according to standards. The purpose of this study was to determine the relationship between the knowledge and attitudes of cleaning service and the use of personal protective equipment (PPE) in handling solid medical waste at Rotinsulu Lung Hospital Bandung. This study uses the observational analytical method with a cross-sectional study approach. The sample in this study was 30 respondents using the purposive sampling technique. The research instrument used was a knowledge questionnaire, an attitude questionnaire, and an observation sheet on the use of personal protective equipment. Statistical test results using the chi square test on the relationship between knowledge and the use of personal protective equipment obtained the number 0.016, which means that there is a relationship between knowledge and the use of personal protective equipment. The results of attitudes towards the use of personal protective equipment obtained a value of 0.005, which means there is a relationship between attitudes towards the use of personal protective equipment. Based on this study, it can be concluded that there is a relationship between knowledge and attitudes towards the use of personal protective equipment. It is recommended for hospitals to carry out training activities related to infection prevention and control and the use of personal protective equipment (PPE) for cleaning service in order to increase understanding of the benefits and functions of PPE.